OP031 Clinical effectiveness, safety and immunogenicity of anti-TNF therapy in Crohn's disease: 12-month data from the PANTS study. (16th January 2018) - Kennedy, N A; Heap, G; Hamilton, B; Walker, G J; Bewshea, C; Bouri, S; Goodhand, J; ,; Ahmad, T
Abstract: Background: PANTS (Personalised Anti-TNF Therapy in Crohn's disease [CD]) is a 3-year prospective observational UK-wide study investigating primary non-response (PNR), loss of response and adverse drug reactions to infliximab (IFX: Remicade [REM], CT-P13) and adalimumab (ADL: Humira). We now report the week 54 clinical effectiveness and safety outcomes, and immunogenicity data to date. Methods: Inclusion criteria included: CD patients aged ≥6 years, active inflammatory disease (raised CRP [>3 mg/l] or calprotectin [≥50 µg/g]) and no prior anti-TNF therapy. PNR was defined at week 12–14 as a requirement for ongoing steroids, or both HBI failed to fall by ≥3 points or to ≤4 and CRP failed to fall by ≥50% or to ≤3 mg/l. Remission was defined at weeks 14 and 54 as HBI ≤3 points and CRP ≤3 mg/l and no concomitant steroids. Patients who stopped drug other than for elective withdrawal, pregnancy or loss to follow-up were regarded as treatment failures for subsequent endpoints. In children, short PCDAI was used. Drug (DL) and anti-drug antibody (ADA) levels were measured using the IDKmonitor® drug tolerant ELISA assays. Immunogenicity was defined as ADA titre ≥10 AU/ml + undetectable DL. Results: A total of 1601 (49% male, median age 33 years [IQR 23–47]) eligible patients were recruited from 118 sites. Patients were treated with IFX (751 [47%]: REM, 200 [12%] CT-P13) or ADL (650 [41%]). Baseline characteristics included: median disease duration 3 years (IQR 1–10); steroids 27%, azathioprine 44%, mercaptopurine 8%, methotrexate 5%; median CRP in IFX 9 mg/l (IQR CI 3–24) and 6 mg/l (IQR 2–14) in ADL. PNR at week 12–14 was 21%, 21% and 26% in the REM, CT-P13 and ADL treated patients respectively. PNR was associated with older age ( p = 0.0004), higher BMI ( p = 0.03) and low DL ( p < 0.0001 for IFX and ADL). Week 54 remission rate was 40%, 40% and 34% of the REM, CT-P13 and ADL treated patients, respectively. At week 54, the immunogenicity rate for REM, CT-P13 and ADL was 26%, 28% and 11% rising to 42%, 38% and 23% by 3 years respectively (IFX vs. ADL p < 0.0001, Remicade vs. CT-P13 p = 0.25). Immunogenicity was associated with non-remission at week 54 ( p < 0.0001 for both IFX and ADL). Immunomodulator use reduced the risk of immunogenicity for both IFX (HR=0.37, p < 0.0001) and ADL (HR=0.34, p < 0.0001). 140 patients (9%) withdrew from drug for serious adverse events including five who died, three from CD and two from possibly drug-related acute respiratory illness. Conclusions: This is the largest prospective real-life study of anti-TNF therapy in IBD. We report the clinical effectiveness and safety of REM, CT-P13, and ADL and the rate and clinical impact of immunogenicity. This cohort provides a unique bioresource for down-stream multi-omic studies investigating personalised approaches to anti-TNF therapy.